Depressive symptoms and cardiovascular disease: a population-based study of older adults in rural Burkina Faso - Brinkmann, Ben; Payne, Collin F.; Kohler, Iliana; Harling, Guy; Davies, Justine; Witham, Miles; Siedner, Mark J.; Sié, Ali; Bountogo, Mamadou; Ouermi, Lucienne; Coulibaly, Boubacar; Bärnighausen, Till (BMJ open, 2020)
Objectives To contribute to the current understanding of depressive disorders in sub-Saharan African (SSA) countries by examining the association of depressive symptoms with cardiovascular and cardiometabolic conditions in a population-based study of middle-aged and older adults in rural Burkina Faso. - Setting This study was conducted in the Nouna Health and Demographic Surveillance System in north-western Burkina Faso, in a mixed rural and small-town environment. The data were obtained between May and July 2018. - Participants Consenting adults over 40 years of age (n=3026). - Primary and secondary outcome measures Depressive symptoms were assessed using the Patient Health Questionnaire depression module (PHQ-9). Chronic cardiometabolic conditions were assessed via a lipid panel and glycated haemoglobin measures from serum, alongside anthropometry and blood pressure measurements and a self-reported questionnaire. Multivariable linear regression was used to test the relationship between depressive symptoms and cardiovascular/cardiometabolic conditions after controlling for sociodemographic factors. - Results Depressive symptoms were not associated with the metabolic syndrome (standardised beta coefficient=0.00 (95% CI −0.04 to 0.03)), hypertension (beta=0.01 (95% CI −0.02 to 0.05)), diabetes mellitus (beta=0.00 (95% CI −0.04 to 0.04)) and past diagnosis of elevated blood pressure or blood sugar. Prior stroke diagnosis (beta=0.04 (95% CI 0.01 to 0.07)) or heart disease (beta=0.08 (95% CI 0.05 to 0.11)) was positively associated with the standardised PHQ-9 score as were self-reported stroke symptoms. - Conclusion Objectively measured cardiometabolic conditions had no significant association with depressive symptoms in an older, poor, rural SSA population, in contrast to observations in high income countries. However, consequences of cardiovascular disease such as stroke and heart attack were associated with depressive symptoms in older adults in Burkina Faso.